2009
DOI: 10.1182/blood.v114.22.3723.3723
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Proliferative and Apoptotic Activity of Lenalidomide in Combination with Rituximab in Follicular Lymphoma: An in Vitro and Ex Vivo Analysis in Follicular Lymphoma Cells.

Abstract: 3723 Poster Board III-659 Introduction Rituximab-containing chemoimmunotherapy regimens have become the standard of care for first line therapy of follicular lymphoma (FL). Despite such intensive treatments most FL patients will continue to relapse and prognosis for those not cured with initial therapy remains poor. Lenalidomide is an immunomodulatory agent; in several in vitro and ex vivo lymphoma models lenalidomide has shown an ability to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In an effort to improve response rates, lenalidomide was combined with rituximab in in vitro lymphoma models. The laboratory studies demonstrated synergistic antitumour effects with the combination, which were partly achieved through the enhancement of antibody-dependent cellular cytotoxicity (ADCC) (Hernandez-Ilizaliturri et al, 2005;Reddy et al, 2008;Wu et al, 2008;Gandhi et al, 2009;Zhang et al, 2009). In addition, preliminary clinical data with this combination has shown promising results in several ongoing phase II clinical trials (Dutia et al, 2010;Zinzani et al, 2011;Leonard et al, 2012;Sacchi et al, 2012).…”
mentioning
confidence: 99%
“…In an effort to improve response rates, lenalidomide was combined with rituximab in in vitro lymphoma models. The laboratory studies demonstrated synergistic antitumour effects with the combination, which were partly achieved through the enhancement of antibody-dependent cellular cytotoxicity (ADCC) (Hernandez-Ilizaliturri et al, 2005;Reddy et al, 2008;Wu et al, 2008;Gandhi et al, 2009;Zhang et al, 2009). In addition, preliminary clinical data with this combination has shown promising results in several ongoing phase II clinical trials (Dutia et al, 2010;Zinzani et al, 2011;Leonard et al, 2012;Sacchi et al, 2012).…”
mentioning
confidence: 99%